Modul Praktikum Fisika Berbasis Pendekatan Saintifik dengan QR Code Pada Pokok Bahasan Listrik Magnet: Physics Practicum Module Based on a Scientific Approach with QR Codes on the Topic of Electromagnetism - Miza, Sri Aswaidar; Dasmo, Dasmo (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This research aims to design, develop, and assess the feasibility of a practicum module as a guide for laboratory activities using a scientific approach, enhanced with a QR code feature for the topic of electromagnetism. The method used is Research and Development (R&D) with a 4-D development model approach. Data analysis was conducted descriptively by calculating the percentage of validation results from experts. The validation results showed that the module obtained an average score of 87% from the subject matter expert, 90% from the media expert, and 80% from the language expert. These findings indicate that the scientific-based practicum module integrated with QR codes is in the "good" category and is feasible for implementation in school learning activities.